2019
DOI: 10.1103/physrevlett.122.072503
|View full text |Cite
|
Sign up to set email alerts
|

Preequilibrium Asymmetries in the Pu239(n,f) Prompt Fission Neutron Spectrum

Abstract: The physical properties of neutrons emitted from neutron-induced fission are fundamental to our understanding of nuclear fission. However, while state-of-the-art fission models still incorporate isotropic fission neutron spectra, it is believed that the pre-equilibrium pre-fission component of these spectra is strongly anisotropic. The lack of experimental guidance on this feature has not motivated incorporation of anisotropic neutron spectra in fission models, though any significant anisotropy would impact de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…It was suggested in Ref. (18) that this feature is the pre-equilibrium component of the PFNS as it appears to match predictions of this PFNS component given in Refs. (34; 35; 36; 37).…”
Section: Comparison Of Experimental Resultssupporting
confidence: 76%
“…It was suggested in Ref. (18) that this feature is the pre-equilibrium component of the PFNS as it appears to match predictions of this PFNS component given in Refs. (34; 35; 36; 37).…”
Section: Comparison Of Experimental Resultssupporting
confidence: 76%
“…These results were described in Ref. [11], where it was also shown that these counts appear to have an angular distribution consistent with a pure inelastic scattering reaction, providing experimental support to the theory that there is little-to-no cor- Figure 3. Third-chance fission and pre-equilibrium PFNS features observed by the Chi-Nu experiment for neutron-induced fission of 235 U (left) and 239 Pu (right) are shown here.…”
Section: Multi-chance and Pre-equilibrium Pfns Featuressupporting
confidence: 71%
“…1 of Ref. [11]. The evolution of the PFNS with increasing incident neutron energy is the convolution of these various possible fission paths, each of which may produce different features in the measured neutron spectrum in coincidence with fission.…”
Section: Introductionmentioning
confidence: 94%
“…These newer results include a large fraction of the PFNS, for fast neutroninduced fission of both 235 U and 239 Pu. Pre-equilibrium neutron distributions in the fission of 239 Pu have been reported previously [22], and these features as well as other features in the PFNS for incoming neutron energies above 5 MeV are reported elsewhere in this volume [23].…”
Section: Introductionmentioning
confidence: 70%